Making product decisions in Citra (M) Sdn Bhd - Abu Kasim, Nor Aziah; Abdul Hamid, Mohamed Ali; Wah, L. Y. (Universiti Putra Malaysia Press, 2008)
This case describes the dilemma of Citra (M) Sdn Bhd in making product decisions. This dilemma arises as a result of the need to respond to an urgent order of the 14” colour picture tubes from its headquarters in Korea. These tubes were intended to solve the inadequate production problem of Citra (China) whose production had been disrupted by an explosion. On one hand, satisfying this request might disrupt Citra (M) Sdn Bhd’s production plan due to capacity constraints. On the other hand, accepting this order represents an opportunity to tap the vast market in China. Thus, in spite of the capacity constraints and the possible disruption to its production plan, the General Manager of Citra (M) Sdn Bhd asked himself, “How could I possibly reject this order from China?”.